2015
DOI: 10.1149/2.0021508jes
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Synthesis, Sintering Issues, and Chemical Stability of BaZr0.1Ce0.7Y0.1Yb0.1O3-δProton Conducting Electrolyte for SOFCs

Abstract: Fundamentals of synthesis, sintering issues, and chemical stability of BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb) proton conducting electrolyte material were studied. Solid state reaction (SSR) and glycine nitrate process (GNP) methods were used to synthesize BZCYYb powders. The GNP method produced powders with higher purity and smaller particle size in reduced heat-treatment time and temperature. It was found that BZCYYb material, despite its high proton conductivity, has surprisingly high tendency to react … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…[11][12][13][14][15] The stability and compatibility between BZCYYb and BSCF at intermediate temperature have been studied before. 11 In order to verify the chemical compatibility between LSCF and BZCYYb under cell fabrication condition, powders of the two materials with weight ratio of 7:3 were intimately mixed and exposed to ambient air at typical LSCF-BZCYYb cathode firing temperature of 1000…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] The stability and compatibility between BZCYYb and BSCF at intermediate temperature have been studied before. 11 In order to verify the chemical compatibility between LSCF and BZCYYb under cell fabrication condition, powders of the two materials with weight ratio of 7:3 were intimately mixed and exposed to ambient air at typical LSCF-BZCYYb cathode firing temperature of 1000…”
Section: Methodsmentioning
confidence: 99%
“…12 Then, ∼0.16 mm 2 cathodes were brush painted onto both sides of the sintered BZCYYb pellets with pure silver paste, LSCF paste, mixed LSCF-BZCYYb paste (LSCF: BZCYYb weight ratio of 7:3), and BSCF paste, respectively (Please refer to 11 for formulation of typical cathode pastes used). All painted samples were fully dried in an air oven at 100…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] In comparison, proton conducting oxides, many of which are perovskite-structured, offer higher ionic conductivity with low electronic transport number as well as lower activation energy at intermediate temperature. [10][11][12][13][14][15][16] As a result, they are regarded as the preferred electrolyte for IT-SOFC. 17 For IT-SOFC, the cathode process is generally regarded as the rate-limiting step due to its high activation energy compared to the electrolyte.…”
Section: 2mentioning
confidence: 99%
“…Indeed, a significant phase decomposition of BZCYYb perovskite phase into BaCO 3 and CeO 2 phase in 50% CO 2 and 50% H 2 atmosphere at 750°C, which is higher than this study, was reported. 13) 3.2 Phase change of BZCYYb-Ni after exposure to CO 2 and H 2 -CO 2 atmosphere…”
Section: Phase Change Of Bzcyyb After Exposure To Co 2 and H 2 -Co 2 mentioning
confidence: 99%
“…9),12) However, other studies reported on its reactivity with carbon dioxide. 13), 14) Thus, the chemical stability of this BZCYYb proton conductor is still not clear. Furthermore, the effect of nickel sintering aid on chemical stability is also important because nickel is dissolved into the electrolyte in the case of anode-support-type cell.…”
Section: Introductionmentioning
confidence: 99%